In vitro activity of N-formimidoyl thienamycin (MK0787), a crystalline derivative of thienamycin. - Horadam, V W (1980)
N-Formimidoyl thienamycin (MK0787) is a derivative of thienamycin, a unique, new beta-lactam antibiotic. Its activity against 285 aerobic and facultatively anaerobic clinical isolates was compared with the activities of cephalothin, ampicillin, penicillin G, ticarcillin, and tobramycin. All of the 285 isolates, with the exception of 1 Staphylococcus epidermidis isolate, were inhibited by a concentration of N-formimidoyl thienamycin of less than or equal to 8 micrograms/ml. More than 50% of all isolates were inhibited by the lowest concentration of N-formimidoyl thienamycin tested (0.125 micrograms/ml); 98% of Staphylococcus aureus and 80% of S. epidermidis isolates were inhibited by N-formimidoyl thienamycin at a concentration of 0.125 micrograms/ml. Only 2 of 45 enterococci were not inhibited by 1 microgram of N-formimidoyl thienamycin per ml, and this drug was the most active agent tested against 162 gram-negative bacilli. It inhibited more than 95% of the gram-negative isolates at a concentration of less than or equal to 2 micrograms/ml. N-Formimidoyl thienamycin was as active or more active than tobramycin against Escherichia coli, Pseudomonas aeruginosa, and Proteus mirabilis and substantially more active than ticarcillin. All 16 isolates of Klebsiella pneumoniae were inhibited by less than or equal to 0.5 micrograms of N-formimidoyl thienamycin per ml. The marked in vitro activity of this drug against a wide variety of clinical isolates makes it a promising new antibiotic.